A microbial self-repairing cement-based material based on surface modified basalt fiber and preparation method thereof
By nano-silica modification of basalt fibers, the problem of fibers being unfavorable to bacterial adhesion is solved, and the self-healing rate and mechanical properties of microbial self-healing concrete are significantly improved.
Patent Information
- Application Number
- CN202410729409.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-06-06
AI Technical Summary
The existing basalt fibers and bacteria used in microbial self-healing concrete have the problem that fibers are not conducive to bacterial adhesion and deposition, and their performance has not yet achieved ideal results.
By nanosilica modification of basalt fibers, the roughness and negative charge of the fiber surface are increased, the compatibility of the fiber with cement mortar is improved, and bacterial adhesion and metabolic activities are promoted.
The modified basalt fibers significantly improve the interface compatibility and bondability with cement mortar, enhance the adhesion ability of bacteria and calcium carbonate generation, and significantly improve the self-healing rate of cracks and the mechanical properties of concrete.
Smart Images

Figure CN118598591B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials. Background Art
[0002] Concrete is widely used in engineering construction due to its high strength and durability. However, concrete is prone to cracking under the influence of various factors such as load, temperature difference and material shrinkage. The presence of cracks will cause moisture and corrosive ions (Cl - and SO4 2- ) provides a channel, aggravating the corrosion of the steel bars inside the concrete, thereby shortening the service life of the structure. Therefore, crack repair is very important. Traditional manual repair methods are not thorough for deeper cracks, and remote cracks cannot be completely repaired by manual methods due to the difficulty in exploration. In response to the above problems, researchers have proposed methods for self-healing of concrete cracks. Common concrete self-healing methods include mineral admixtures, microbial self-healing, microcapsules, etc. Microbial self-healing has attracted attention due to its low carbon and environmental protection characteristics and good crack healing effect.
[0003] Microbial self-healing concrete technology (MICP) mainly refers to the process in which bacteria consume calcium-containing nutrients through their own metabolism to produce calcium carbonate to heal cracks. However, the highly alkaline environment inside concrete and the continuous hydration of cement gradually compress the living space of bacteria inside concrete, which will threaten the survival of bacteria. Jonkers et al. (HM Jonkers, A. Thijssen, G. Muyzer, O. Copuroglu, E. Schlangen, Application of bacteria as self-healing agent for the development of sustainable concrete, Ecological Engineering 36 (2) (2010) 230-235) found that bacteria lose the ability to mineralize and precipitate in the cement matrix after 28 days of curing in concrete. Therefore, protecting bacterial spores and ensuring their survival in concrete is one of the focuses of MICP technology research. Studies have found that microcapsules can immobilize bacteria, but their production process is complicated and the cost is high. Porous materials such as expanded perlite, zeolite, and diatomaceous earth have been proven to effectively adsorb and protect bacterial spores and have good healing effects. With the in-depth study of porous materials as carriers, the challenges posed by bacterial survival have been solved to meet the application requirements in practical engineering.
[0004] The width of the crack is another important factor in improving the practical application effect of MICP technology. Studies have shown that when the crack width is greater than 500 μm, the calcium carbonate produced by microbial mineralization is not enough to connect the two sides of the crack to achieve complete healing of the crack. Adding fibers to concrete can improve the toughness and strength of microbial self-healing concrete. Kunamineni et al. (K. Vijay, M. Murmu, Self-repairing of concrete cracks by using bacteria and basalt fiber, SN Applied Sciences 1 (11) (2019) 1344) used basalt fiber and bacteria for microbial self-healing concrete. The results showed that basalt fiber effectively controlled the development of cracks and promoted the self-healing of larger microcracks through bridging. It is well known that bacterial biofilm is the basis for bacterial survival. The biofilm adheres to the carrier to achieve large-scale reproduction of bacteria. Under the action of high-temperature melting, the fiber surface of basalt fiber presents a smooth cylindrical morphology, and due to the lack of hydrophilic groups on the fiber surface, the fiber has hydrophobicity and electronegativity. Since the bacterial surface in most bacterial solutions carries negative charges, it is not conducive to the attachment and deposition of bacteria on the surface of basalt fibers, which will be detrimental to the fiber's promotion of self-healing of wider cracks. Therefore, in order to obtain better self-healing properties, surface modification of basalt fibers is very necessary. Summary of the invention
[0005] The present invention aims to solve the problem that the existing basalt fiber and bacteria are used in microbial self-healing concrete, that is, the basalt fiber is not conducive to the attachment and deposition of bacteria on the surface of the basalt fiber, and the performance still needs to be improved, and further provide a microbial self-healing cement-based material based on surface modified basalt fiber and a preparation method thereof.
[0006] A microbial self-healing cement-based material based on surface modified basalt fiber, which is composed by mass of 400 to 500 parts of water, 8 to 15 parts of calcium lactate, 2 to 4 parts of water reducer, 900 to 1000 parts of cement, 35 to 40 parts of microbial self-healing agent, 3 to 6 parts of surface modified basalt fiber and 1400 to 2000 parts of standard sand.
[0007] A method for preparing a microbial self-repairing cement-based material based on surface-modified basalt fiber is carried out according to the following steps:
[0008] 1. Preparation of microbial self-healing agents:
[0009] The bacillus pseudofirmus bacterial liquid is mixed with expanded perlite and then the expanded perlite after the soaking is dried to obtain a microbial self-healing agent;
[0010] 2. Surface modification of basalt fiber:
[0011] ① Immersing the basalt fiber in a hydrogen peroxide solution to perform surface oxidation treatment on the fiber, and then washing and drying to obtain surface-oxidized basalt fiber;
[0012] ② Immersing the basalt fiber after surface oxidation treatment in a hydrochloric acid solution for etching, and then washing and drying to obtain the etched basalt fiber;
[0013] ③ Add the silane coupling agent to anhydrous ethanol, then add nano-silicon dioxide and mix evenly to obtain a nano-silicon dioxide modifier;
[0014] ④ Immersing the etched basalt fiber in a nano-silicon dioxide modifier for ultrasonic treatment, and finally drying to obtain surface-modified basalt fiber;
[0015] 3. Mixing and curing of mortar:
[0016] ① Weigh 400 to 500 parts of water, 8 to 15 parts of calcium lactate, 2 to 4 parts of water reducer, 900 to 1000 parts of cement, 35 to 40 parts of microbial self-healing agent, 3 to 6 parts of surface-modified basalt fiber and 1400 to 2000 parts of standard sand by mass;
[0017] ② Mix the weighed water, calcium lactate and water reducing agent to obtain a mixed solution;
[0018] ③ Mix the weighed cement, microbial self-healing agent, surface-modified basalt fiber and standard sand, add the mixed solution and stir thoroughly to obtain mortar, and cure the mortar under standard curing conditions to obtain a microbial self-healing cement-based material based on surface-modified basalt fiber.
[0019] The beneficial effects of the present invention are:
[0020] (1) The nano-silica modifier used in the present invention has a simple preparation process, low material price, and fast preparation speed. After surface acid etching and nano-silica modification, the specific surface area of basalt fiber is significantly increased, and the compatibility of fiber and cement mortar is effectively improved. It can be mass-produced and applied to actual projects.
[0021] (2) The present invention uses nano-silicon dioxide to treat the surface of basalt fiber. The fiber surface roughness is significantly increased from a macroscopic and microscopic perspective, which increases the friction coefficient between the fiber and the cement paste. At the same time, since nano-silicon dioxide has volcanic ash reactivity, the Ca in the pore solution around the fiber and in the cement mortar increases. 2+ and OH -The reaction occurs to generate calcium silicate hydrate (CSH) gel, which significantly improves the pore structure of the transition zone between the fiber and cement paste interface and improves the interface compatibility. Combining the above two aspects, the synergy and interface adhesion between the modified basalt fiber and cement paste are significantly improved. The flexural strength and compressive strength of the final specimen are significantly improved.
[0022] (3) The present invention uses nano-silicon dioxide to modify basalt fibers. Through macroscopic crack observation, it is found that the modified fibers have an obvious bridging effect and can provide a deposition direction for the healing products. Moreover, the modified fiber surface is rough, which is conducive to the attachment of bacteria, and provides more nucleation sites for the attachment of bacterial metabolic calcium carbonate and hydration products. When the specimen is not mixed with fibers, bacteria can only metabolize from both sides of the crack to gradually produce calcium carbonate to heal the cracks, while the modified fibers can provide nucleation sites and deposition paths, so that bacteria attach to the fiber surface at the crack to carry out metabolic activities to produce calcium carbonate and deposit along the fiber direction to heal the cracks. Finally, the position containing the modified fiber at the crack completes the healing first, which significantly improves the early healing rate of the crack. Through microscopic morphological observation, it is found that the surface roughness of the fiber is significantly increased, and the nano-silicon dioxide attached to the fiber surface has volcanic ash reactivity, which reacts with the Ca in the pore solution in the mortar. 2+ and OH - The reaction generates a clear CSH shell that wraps the fiber surface. Compared with the unmodified fiber, the negative charge and hydrophobicity of the modified fiber surface are significantly improved. The CSH shell on the fiber surface is conducive to the attachment of bacteria, which metabolize on the fiber surface to generate a large amount of calcium carbonate. Finally, when the healing age is 14 days, the crack healing rate reaches 100%.
[0023] (4) The present invention improves the interfacial compatibility between the fiber and the mortar and effectively improves the mechanical properties of the mortar specimen by using nano-silicon dioxide to modify the surface of the basalt fiber. The CSH shell generated by the volcanic ash reaction of nano-silicon dioxide on the fiber surface effectively promotes more bacteria to adhere to the fiber surface, and a large amount of calcium carbonate is generated on the fiber surface at the cracks, thereby improving the self-healing ability of the cracks in the microbial mortar specimen. Under the coupling effect of modified basalt fiber and microbial self-healing technology, the self-healing ability of the cracks is significantly improved, further improving the durability of the concrete structure, thereby ensuring the safe service of the infrastructure, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The SEM micrographs of the basalt fiber before and after modification in Example 1, (a) is the unmodified basalt fiber, (b) is the surface-modified basalt fiber prepared in step 2④ of Example 1;
[0025] Figure 2Crack observation diagram of the microbial self-repairing cement-based material prepared in Example 1 when the crack healing age is 0, 3, 7 and 14 days;
[0026] Figure 3 These are SEM microscopic images of the crack fillings of the microbial self-repairing cement-based material taken at a healing age of 14 days, (a) is the SEM image of the crack fillings of the control group 2, and (b) is the SEM image of the crack fillings of Example 1. DETAILED DESCRIPTION
[0027] Specific implementation method 1: This implementation method is a microbial self-healing cement-based material based on surface modified basalt fiber, which is composed of 400 to 500 parts of water, 8 to 15 parts of calcium lactate, 2 to 4 parts of water reducer, 900 to 1000 parts of cement, 35 to 40 parts of microbial self-healing agent, 3 to 6 parts of surface modified basalt fiber and 1400 to 2000 parts of standard sand in parts by mass.
[0028] The beneficial effects of this embodiment are:
[0029] (1) The nano-silica modifier used in this embodiment has a simple preparation process, low material price, and fast preparation speed. After surface acid etching and nano-silica modification, the specific surface area of basalt fiber is significantly increased, and the compatibility of fiber and cement mortar is effectively improved. It can be mass-produced and applied to actual projects.
[0030] (2) In this embodiment, nano-silicon dioxide is used to treat the surface of basalt fiber. The fiber surface roughness is significantly increased from a macroscopic and microscopic perspective, which increases the friction coefficient between the fiber and the cement paste. At the same time, since nano-silicon dioxide has volcanic ash reactivity, the Ca in the pore solution around the fiber and in the cement mortar increases. 2+ and OH - The reaction occurs to generate calcium silicate hydrate (CSH) gel, which significantly improves the pore structure of the transition zone between the fiber and cement paste interface and improves the interface compatibility. Combining the above two aspects, the synergy and interface adhesion between the modified basalt fiber and cement paste are significantly improved. The flexural strength and compressive strength of the final specimen are significantly improved.
[0031] (3) This embodiment uses nano-silicon dioxide to modify basalt fibers. Through macroscopic crack observation, it is found that the modified fibers have an obvious bridging effect and can provide a deposition direction for the healing products. Moreover, the modified fiber surface is rough, which is conducive to the attachment of bacteria and provides more nucleation sites for the attachment of bacterial metabolic calcium carbonate and hydration products. When the specimen is not mixed with fibers, bacteria can only metabolize from both sides of the crack to gradually produce calcium carbonate to heal the cracks, while the modified fibers can provide nucleation sites and deposition paths, so that bacteria attach to the fiber surface at the crack to carry out metabolic activities to produce calcium carbonate and deposit along the fiber direction to heal the cracks. Finally, the position containing the modified fiber at the crack completes the healing first, which significantly improves the early healing rate of the crack. Through microscopic morphological observation, it is found that the surface roughness of the fiber is significantly increased, and the nano-silicon dioxide attached to the fiber surface has volcanic ash reactivity, which reacts with the Ca in the pore solution in the mortar. 2+ and OH - The reaction generates a clear CSH shell that wraps the fiber surface. Compared with the unmodified fiber, the negative charge and hydrophobicity of the modified fiber surface are significantly improved. The CSH shell on the fiber surface is conducive to the attachment of bacteria, which metabolize on the fiber surface to generate a large amount of calcium carbonate. Finally, when the healing age is 14 days, the crack healing rate reaches 100%.
[0032] (4) This embodiment improves the interfacial compatibility between the fiber and the mortar by using nano-silicon dioxide to modify the surface of the basalt fiber, thereby effectively improving the mechanical properties of the mortar specimen. The CSH shell generated by the volcanic ash reaction of nano-silicon dioxide on the fiber surface effectively promotes more bacteria to adhere to the fiber surface, and a large amount of calcium carbonate is generated on the fiber surface at the cracks, thereby improving the self-healing ability of the cracks in the microbial mortar specimen. Under the coupling effect of modified basalt fiber and microbial self-healing technology, the self-healing ability of the cracks is significantly improved, further improving the durability of the concrete structure, thereby ensuring the safe service of the infrastructure, and has broad application prospects.
[0033] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the surface-modified basalt fiber is prepared from basalt fiber and nano-silicon dioxide; the microbial self-healing agent is prepared from Bacillus pseudofirmus liquid and expanded perlite. The rest is the same as specific embodiment 1.
[0034] Specific implementation method three: This implementation method is a method for preparing a microbial self-repairing cement-based material based on surface modified basalt fiber, which is characterized by being carried out according to the following steps:
[0035] 1. Preparation of microbial self-healing agents:
[0036] The bacillus pseudofirmus bacterial liquid is mixed with expanded perlite and then the expanded perlite after the soaking is dried to obtain a microbial self-healing agent;
[0037] 2. Surface modification of basalt fiber:
[0038] ① Immersing the basalt fiber in a hydrogen peroxide solution to perform surface oxidation treatment on the fiber, and then washing and drying to obtain surface-oxidized basalt fiber;
[0039] ② Immersing the basalt fiber after surface oxidation treatment in a hydrochloric acid solution for etching, and then washing and drying to obtain the etched basalt fiber;
[0040] ③ Add the silane coupling agent to anhydrous ethanol, then add nano-silicon dioxide and mix evenly to obtain a nano-silicon dioxide modifier;
[0041] ④ Immersing the etched basalt fiber in a nano-silicon dioxide modifier for ultrasonic treatment, and finally drying to obtain surface-modified basalt fiber;
[0042] 3. Mixing and curing of mortar:
[0043] ① Weigh 400 to 500 parts of water, 8 to 15 parts of calcium lactate, 2 to 4 parts of water reducer, 900 to 1000 parts of cement, 35 to 40 parts of microbial self-healing agent, 3 to 6 parts of surface-modified basalt fiber and 1400 to 2000 parts of standard sand by mass;
[0044] ② Mix the weighed water, calcium lactate and water reducing agent to obtain a mixed solution;
[0045] ③ Mix the weighed cement, microbial self-healing agent, surface-modified basalt fiber and standard sand, add the mixed solution and stir thoroughly to obtain mortar, and cure the mortar under standard curing conditions to obtain a microbial self-healing cement-based material based on surface-modified basalt fiber.
[0046] Specific embodiment 4: This embodiment is different from the specific embodiment 3 in that the concentration of the Bacillus pseudofirmus liquid in step 1 is 3.5×10 9 Cells / mL~4.0×10 9 cells / ml; the water absorption rate of the expanded perlite under atmospheric pressure described in step 1 is 250% to 300%, and the particle size is 2mm to 4mm; in step 1, the Bacillus pseudofirmus bacterial solution and the expanded perlite are mixed and soaked for 24h to 48h under sterile and room temperature conditions. The rest is the same as the specific implementation method three.
[0047] Specific implementation method 5: This implementation method is different from specific implementation method 3 or 4 in that: the length of the basalt fiber in step 2① is 10mm-14mm, and the diameter is 15μm-20μm; the mass percentage of the hydrogen peroxide solution in step 2① is 3%-5%; the fiber surface oxidation treatment in step 2① is specifically treated at room temperature for 2h-3h. Others are the same as specific implementation method 3 or 4.
[0048] Specific embodiment 6: This embodiment is different from any one of specific embodiments 3 to 5 in that: the concentration of the hydrochloric acid solution in step 2② is 0.8 mol / L to 1 mol / L; the etching in step 2② is specifically carried out at a temperature of 40℃ to 45℃ for 1.5h to 2h. The rest is the same as specific embodiments 3 to 5.
[0049] Specific embodiment 7: This embodiment is different from any one of specific embodiments 3 to 6 in that: the silane coupling agent described in step 2 ③ is KH-550; the mass percentage of the silane coupling agent in the nano-silica modifier described in step 2 ③ is 0.7% to 0.8%; the mass percentage of nano-silica in the nano-silica modifier described in step 2 ③ is 3% to 4%, and the particle size of the nano-silica is 1nm to 100nm. Others are the same as specific embodiments 3 to 6.
[0050] Specific embodiment 8: This embodiment differs from any one of specific embodiments 3 to 7 in that: the volume ratio of the etched basalt fiber to the nano-silicon dioxide modifier in step 2 ④ is 1:(10-15); the ultrasonic treatment in step 2 ④ is specifically carried out for 30 min to 45 min under the condition of an ultrasonic resonance frequency of 20 kHz to 30 kHz. The rest is the same as specific embodiments 3 to 7.
[0051] Specific embodiment 9: This embodiment is different from any one of specific embodiments 3 to 8 in that the water reducing agent in step 3① is a lignin sulfonate water reducing agent or a naphthalene sulfonate water reducing agent. The rest is the same as specific embodiments 3 to 8.
[0052] Specific implementation ten: This implementation is different from Specific implementations one to nine in that: Step three ③ The weighed cement, microbial self-healing agent, surface-modified basalt fiber and standard sand are sequentially placed in a cement mortar mixer, dry mixed for 30s to 40s at room temperature and a rotation speed of 140r / min to 142r / min, and then the mixed solution is added, and then slowly stirred for 1.5min to 1.8min at room temperature and a rotation speed of 140r / min to 142r / min, and then quickly stirred for 2min to 2.5min at room temperature and a rotation speed of 285r / min to 288r / min to obtain mortar; Step three ③ The curing under standard curing conditions is specifically curing for 24h to 36h at a temperature of 20±2℃ and a humidity of>99%. The rest is the same as Specific implementations three to nine.
[0053] The following examples are used to verify the beneficial effects of the present invention:
[0054] Embodiment 1:
[0055] A method for preparing a microbial self-repairing cement-based material based on surface-modified basalt fiber is carried out according to the following steps:
[0056] 1. Preparation of microbial self-healing agents:
[0057] The bacillus pseudofirmus bacterial liquid is mixed with expanded perlite and then the expanded perlite after the soaking is dried to obtain a microbial self-healing agent;
[0058] 2. Surface modification of basalt fiber:
[0059] ① Immersing the basalt fiber in a hydrogen peroxide solution to perform surface oxidation treatment on the fiber, and then washing and drying to obtain surface-oxidized basalt fiber;
[0060] ② Immersing the basalt fiber after surface oxidation treatment in a hydrochloric acid solution for etching, and then washing and drying to obtain the etched basalt fiber;
[0061] ③ Add the silane coupling agent to anhydrous ethanol, then add nano-silicon dioxide and mix evenly to obtain a nano-silicon dioxide modifier;
[0062] ④ Immersing the etched basalt fiber in a nano-silicon dioxide modifier for ultrasonic treatment, and finally drying to obtain surface-modified basalt fiber;
[0063] 3. Mixing and curing of mortar:
[0064] ① Weigh 500 parts of water, 10 parts of calcium lactate, 2 parts of water reducer, 1000 parts of cement, 38 parts of microbial self-healing agent, 3 parts of surface-modified basalt fiber and 1400 parts of standard sand by mass;
[0065] ② Mix the weighed water, calcium lactate and water reducing agent to obtain a mixed solution;
[0066] ③ Mix the weighed cement, microbial self-healing agent, surface-modified basalt fiber and standard sand, add the mixed solution and stir thoroughly to obtain mortar, and cure the mortar under standard curing conditions to obtain a microbial self-healing cement-based material based on surface-modified basalt fiber.
[0067] The concentration of the Bacillus pseudofirmus liquid in step 1 is 3.5×10 9 cells / ml; the water absorption rate of the expanded perlite at atmospheric pressure described in step one is 300%, and the particle size is 2mm to 4mm; in step one, under sterile and room temperature conditions, the Bacillus pseudofirmus bacterial solution is mixed with the expanded perlite and immersed for 24h.
[0068] The Bacillus pseudofirmus bacterial solution described in step 1 is specifically cultured according to the following steps: using purified water, beef extract, peptone and sodium chloride to prepare a bacterial liquid culture medium, wherein the beef extract accounts for 0.5% of the mass of purified water, the peptone accounts for 0.3% of the mass of purified water, and the sodium chloride accounts for 0.5% of the mass of purified water; transplanting the strain into the culture medium, and using a shaker to culture for 48 hours at 25-30°C and 120 rpm. After culturing, a bacterial bacterial solution is obtained, the bacterial solution is placed in a centrifuge and centrifuged at a speed of 6000r / min, the culture solution is removed to obtain bacteria, the bacteria are dispersed in purified water, and the bacterial concentration is measured by a spectrophotometer to be 3.5×10 9 cells / mL.
[0069] The basalt fiber described in step 2① has a length of 12 mm, a diameter of 17.4 μm, an elastic modulus greater than 85 GPa, and a tensile strength greater than 2000 MPa; the mass percentage of the hydrogen peroxide solution described in step 2① is 5%; the fiber surface oxidation treatment described in step 2① is specifically carried out at room temperature for 2 hours.
[0070] The concentration of the hydrochloric acid solution in step 2② is 1 mol / L; the etching in step 2② is specifically carried out at a temperature of 45° C. for 1.5 hours.
[0071] The silane coupling agent described in step 2③ is KH-550; the mass percentage of the silane coupling agent in the nano-silica modifier described in step 2③ is 0.75%; the mass percentage of nano-silica in the nano-silica modifier described in step 2③ is 3%, and the particle size of the nano-silica is 1nm to 100nm.
[0072] The volume ratio of the etched basalt fiber to the nano-silicon dioxide modifier in step 2④ is 1:10; the ultrasonic treatment in step 2④ is specifically carried out for 30 minutes at an ultrasonic resonance frequency of 23 kHz.
[0073] The water reducer described in step 3① is polycarboxylic acid high performance water reducer (Q8081PCA); the cement described in step 3① is ordinary Portland cement (OPC); the standard sand described in step 3① is Chinese ISO standard sand.
[0074] Step 3③ Put the weighed cement, microbial self-healing agent, surface-modified basalt fiber and standard sand into the cement mortar mixer in turn, dry mix for 30 seconds at room temperature and a speed of 140 r / min, then add the mixed solution, and then slowly stir for 90 seconds at room temperature and a speed of 140 r / min, and then quickly stir for 2 minutes at room temperature and a speed of 285 r / min to obtain mortar.
[0075] The curing under standard curing conditions described in step 3③ is specifically curing for 24 hours at a temperature of 20±2°C and a humidity of >99%.
[0076] Control group 1: This comparative experiment is different from Example 1 in that step 2 is eliminated and in step 3, the surface-modified basalt fiber is replaced with unmodified basalt fiber. The rest is the same as Example 1.
[0077] Control group 2: This comparative experiment differs from Example 1 in that step 1 is eliminated and in step 3, the microbial self-healing agent is replaced with expanded perlite without encapsulated bacteria. The rest is the same as Example 1.
[0078] Control group 3: This comparative experiment differs from Example 1 in that: Steps 1 and 2 are eliminated, and in Step 3, the surface-modified basalt fiber is replaced with unmodified basalt fiber; in Step 3, the microbial self-healing agent is replaced with expanded perlite without encapsulated bacteria. Others are the same as in Example 1.
[0079] Figure 1 The SEM micrographs of the basalt fiber before and after modification in Example 1 are shown in Figure 1. (a) is the unmodified basalt fiber, and (b) is the surface-modified basalt fiber prepared in step 2④ of Example 1. Figure 1 (a) It can be seen that the surface of the unmodified fiber is smooth, while Figure 1 (b) It can be seen that after the fiber is modified, the surface loading of nano-silica particles significantly increases the roughness of the fiber surface.
[0080] Table 1 Mechanical properties of microbial self-repairing cement-based materials prepared in Example 1 and the control group
[0081] sample 28-day compressive strength (MPa) 28-day flexural strength (MPa) Example 1 42.3 7.7 Control group 1 40.7 6.9 Control group 2 37.8 6.6 Control group 3 34.5 6.4
[0082] The mechanical properties test was carried out according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019); comparing the data in Table 1, it can be seen that the mechanical properties of the specimens are improved after adding the microbial self-healing agent, and the mechanical properties of the mortar specimens are significantly enhanced under the synergistic effect of the modified basalt fiber and the microbial self-healing agent. Therefore, the microbial self-healing cement-based material based on surface modified basalt fiber in Example 1 has good mechanical properties.
[0083] When the specimen curing age was 28 days, a cement anti-bending and anti-compression integrated machine was used to introduce cracks into the specimen. The preparation process of the specimen cracks is as follows: (1) A steel wire with a diameter of 1 mm and a length of 50 mm is placed at the center of the pressure plate of the testing machine; (2) The specimen is placed on the pressure plate and loaded at a speed of 20 N / s until a crack with a width of 100 μm to 1000 μm is formed, and then the loading is stopped; (3) After the crack preparation is completed, the microbial self-healing cement-based material of Example 1 is placed in water at 30°C for oxygenation and curing for healing, and the remaining specimens are immersed in water (temperature of 23±1°C) for healing and curing. The specific test results are shown in Table 2. Figure 2 and Figure 3 .
[0084] Table 2 Healing rate of cracks in microbial self-repairing cement-based materials prepared in Example 1 and the control group at 3, 7, and 14 days (%)
[0085]
[0086] Comparing the data in Table 2, it can be seen that after adding the microbial self-healing agent, the cracks of the specimens (Example 1 and Control Group 1) can be completely healed after 14 days of curing. When the healing age is 7 days, the healing rate of Example 1 is higher than that of all control groups. It shows that under the synergistic effect of modified basalt fiber and microbial self-healing agent in Example 1, the early healing effect of mortar specimen cracks is significantly enhanced. The healing rate of Control Group 3 was 41.9% after 14 days of healing, indicating that the ability to heal cracks by relying on cement hydration products is limited. The healing rate of Control Group 2 was 88.35% after 14 days of healing. Due to the addition of modified fibers, nucleation sites are provided for the hydration of unhydrated cement particles, which promotes the crack healing effect to be higher than that of Control Group 3 with unmodified fibers added. In summary, the microbial self-healing cement-based material based on surface modified basalt fiber in Example 1 has good crack self-healing ability.
[0087] Figure 2The crack observation diagram of the microbial self-repairing cement-based material prepared in Example 1 when the crack healing age is 0, 3, 7 and 14 days. It can be seen from the figure that in Example 1, when the healing age is 14 days, the cracks of the specimen can be completely healed, and when the age is 3 days and 7 days, the surroundings of the crack containing fibers are preferentially healed, which improves the early healing efficiency of the cracks.
[0088] Figure 3 The SEM microscopic images of the crack fillings of the microbial self-repairing cement-based material taken at the healing age of 14 days, (a) is the SEM image of the crack fillings of the control group 2, and (b) is the SEM image of the crack fillings of Example 1. As shown in Figure (a), the interface transition zone between the modified fiber and the cement paste is tightly bonded. This is because the nano-silica carried on the surface of the modified fiber and the Ca in the pore solution of the mortar 2+ and OH - The reaction to generate calcium silicate hydrate (CSH) changes the pore structure of the interface transition zone between the fiber and cement paste, increases the bonding ability between the fiber and the mortar paste, and significantly improves the mechanical properties of the specimen. As shown in Figure (b), a rough shell and a large amount of calcium carbonate are attached to the fiber surface. This is because the Ca in the pore solution of the nano-silica mortar loaded on the surface of the modified fiber 2+ and OH - The reaction generates calcium silicate hydrate (CSH), which forms a shell on the fiber surface. The original smooth surface of the fiber is wrapped by the CSH shell, which changes the original hydrophobicity and negative charge of the fiber surface. Compared with the unmodified fiber, the modified fiber is more conducive to the attachment of bacteria. More bacteria metabolize on the fiber surface and generate more calcium carbonate. Finally, the cracks were completely healed after 14 days of healing.
Claims
1. A microbial self-repairing cement-based material based on surface modified basalt fiber, characterized in that It consists of 500 parts of water, 10 parts of calcium lactate, 2 parts of water reducing agent, 1000 parts of cement, 38 parts of microbial self-healing agent, 3 parts of surface-modified basalt fiber and 1400 parts of standard sand by mass. The above-mentioned method for preparing a microbial self-repairing cement-based material based on surface modified basalt fiber is carried out according to the following steps:
1. Preparation of microbial self-healing agents: The bacillus pseudofirmus bacterial liquid is mixed with expanded perlite and then the expanded perlite after the soaking is dried to obtain a microbial self-healing agent; 2. Surface modification of basalt fiber: ① Immersing the basalt fiber in a hydrogen peroxide solution to perform surface oxidation treatment on the fiber, and then washing and drying to obtain surface-oxidized basalt fiber; The mass percentage of the hydrogen peroxide solution is 3% to 5%; the fiber surface oxidation treatment is specifically carried out at room temperature for 2h to 3h; ② Immersing the basalt fiber after surface oxidation treatment in a hydrochloric acid solution for etching, and then washing and drying to obtain the etched basalt fiber; The concentration of the hydrochloric acid solution is 0.8 mol / L to 1 mol / L; the etching is specifically carried out at a temperature of 40° C. to 45° C. for 1.5 h to 2 h; ③ Add the silane coupling agent to anhydrous ethanol, then add nano-silicon dioxide and mix evenly to obtain a nano-silicon dioxide modifier; The silane coupling agent is KH-550; the mass percentage of the silane coupling agent in the nano-silicon dioxide modifier is 0.7% to 0.8%; the mass percentage of nano-silicon dioxide in the nano-silicon dioxide modifier is 3% to 4%, and the particle size of the nano-silicon dioxide is 1nm to 100nm; ④ Immersing the etched basalt fiber in a nano-silicon dioxide modifier for ultrasonic treatment, and finally drying to obtain surface-modified basalt fiber; The volume ratio of the etched basalt fiber to the nano-silicon dioxide modifier is 1:(10-15); the ultrasonic treatment is specifically carried out for 30 minutes to 45 minutes under the condition of an ultrasonic resonance frequency of 20kHz to 30kHz; 3. Mixing and curing of mortar: ① Weigh 500 parts of water, 10 parts of calcium lactate, 2 parts of water reducer, 1000 parts of cement, 38 parts of microbial self-healing agent, 3 parts of surface-modified basalt fiber and 1400 parts of standard sand by mass; ② Mix the weighed water, calcium lactate and water reducing agent to obtain a mixed solution; ③ Mix the weighed cement, microbial self-healing agent, surface-modified basalt fiber and standard sand, add the mixed solution and stir thoroughly to obtain mortar, and cure the mortar under standard curing conditions to obtain a microbial self-healing cement-based material based on surface-modified basalt fiber.
2. The microbial self-repairing cement-based material based on surface-modified basalt fiber according to claim 1, characterized in that The concentration of the Bacillus pseudofirmus liquid in step 1 is 3.5×10 9 Cells / mL~4.0×10 9 cells / ml; the water absorption rate of the expanded perlite at atmospheric pressure described in step one is 250% to 300%, and the particle size is 2mm to 4mm; in step one, under sterile and room temperature conditions, the Bacillus pseudofirmus bacterial solution is mixed with the expanded perlite and immersed for 24h to 48h.
3. The microbial self-repairing cement-based material based on surface-modified basalt fiber according to claim 1, characterized in that The basalt fiber described in step 2① has a length of 10 mm to 14 mm and a diameter of 15 μm to 20 μm.
4. The microbial self-repairing cement-based material based on surface-modified basalt fiber according to claim 1, characterized in that The water reducer described in step 3① is a lignin sulfonate water reducer or a naphthalene sulfonate water reducer.
5. The microbial self-repairing cement-based material based on surface-modified basalt fiber according to claim 1, characterized in that Step 3③: Put the weighed cement, microbial self-healing agent, surface-modified basalt fiber and standard sand into the cement mortar mixer in turn, dry mix for 30s to 40s at room temperature and a rotation speed of 140r / min to 142r / min, add the mixed solution, and then slowly stir for 1.5min to 1.8min at room temperature and a rotation speed of 140r / min to 142r / min, and then quickly stir for 2min to 2.5min at room temperature and a rotation speed of 285r / min to 288r / min to obtain mortar; the curing under standard curing conditions described in step 3③ is specifically curing for 24h to 36h at a temperature of 20±2°C and a humidity of >99%.
Citation Information
Patent Citations
High-crack-resistance concrete and preparation method thereof
CN117843312A